The Efektivitas Model Pembelajaran Discovery Learning Ditinjau Dari Kemampuan Berpikir Kritis Siswa Kelas 5 SD - Gustina Dwi Suryaningrum; Mawardi Mawardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
The purpose of conducting this research activity is to determine the level of effectiveness of the Discovery Learning learning model in terms of the critical thinking skills of grade 5 students. The type of research used as a reference in this research is quasi-experimental research (Quasi-Experimental) with a Nonequivalent Control Group design. The population used in this study were Grade 5 students at SD Gugus Dr. Soetomo which is located in the Tengaran District area with a total population of 123 students. The sample in this study was taken based on the Random Sampling Sample technique, where the sample used was 41 students. The data collection instrument uses a rubric for assessing critical thinking skills and test questions. The data analysis technique used is comparative descriptive technique and T-test. The results of data processing show that the t-h???????????????????? value is 3.689 > ????-???????????????????? is 2.024, with a value of Sig. (2-tailed) of 0.000 <0.05. Based on these data it can be concluded that Ho is rejected and Ha is accepted, meaning that the application of the Discovery Learning learning model is significantly effective in cultivating the critical thinking skills of grade 5 students at Gugus Dr. Soetomo.